2019
DOI: 10.1111/pbr.12767
|View full text |Cite
|
Sign up to set email alerts
|

Characterization 3333 of tomato (Solanum lycopersicum) accessions for resistance to phylotype I and phylotype II strains of the Ralstonia solanacearum species complex under high temperatures

Abstract: Bacterial wilt of tomato caused by Ralstonia solanacearum species complex (RSSC) causes substantial yield losses in the tropics and subtropics. Disease management options by chemicals are limited, and host resistance is the cheapest and easiest means of control. However, sources of bacterial wilt resistance in tomato are limited.The disease often coincides with higher temperatures in the tropics, and resistance sources that are more heat stable are particularly valuable for breeding of tropically adapted tomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The accession F 7 80-465-10-pink was the most resistant to Pss1632 (92.5%), while TBL-2 was the most susceptible (100% of symptomatic plants) (Table 1). The resistant and susceptible reactions of the accessions screened in this study were generally in alignment with the previous work of Kunwar et al 12 employing a partly overlapping set of materials. Hai et al 17 reported that LA3501 was resistant to BW strain Pss186 but susceptible to Pss4.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The accession F 7 80-465-10-pink was the most resistant to Pss1632 (92.5%), while TBL-2 was the most susceptible (100% of symptomatic plants) (Table 1). The resistant and susceptible reactions of the accessions screened in this study were generally in alignment with the previous work of Kunwar et al 12 employing a partly overlapping set of materials. Hai et al 17 reported that LA3501 was resistant to BW strain Pss186 but susceptible to Pss4.…”
Section: Resultssupporting
confidence: 88%
“…These results support the extensive body of literature highlighting the complexity of host-pathogen interactions in the tomato-BW pathosystem, as reviewed by Hayward et al 3 . Furthermore, the higher level of virulence of Pss1632 was previously reported 12 . When challenged with Pss4, LS-89 and F7 80 Pink were the most resistant accessions (100% resistant), while Pant Bahar, L390, and LA3501 were the most susceptible (0%) (Table 1).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Wilting percent on L390 was higher than on the moderately resistant cultivar L180 treated with biocontrol. This is not unexpected since the cultivars differ in reaction to infection by R. pseudosolanacearum where L390 is highly susceptible, and L180 is moderately resistant with wilting percent ranging from 90-100% and 40-60%, respectively [15,19,20]. This study found that wilting percent reduced up to 50% for L390 and 10% for L180 when BCA was applied to seedlings (Table 1), indicating that the combination of resistance and BCA can better control BW than either alone.…”
Section: Resultsmentioning
confidence: 62%
“…cerasiforme (Hanson et al, 1998). Breeding bacterial wilt-resistant tomato varieties is difficult because resistance is often dependent on pathogen strain, which is highly affected by environmental conditions such as soil type, temperature, pH and moisture (Wang et al, 1998;Prior et al, 2016;Kunwar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%